(untitled) (Mustansiria Dental Journal, 2018)
The purpose of this in vitro study was to determine whether shear bond strength (SBS) to chemomechanically excavated dentine by Carisolv (CS) differed from the SBS after conventional caries removal by bur (CB), with the use of the following adhesive systems: [Total-etch (TE), etch and Compobond1, etch, prime and bonding resin]; [Self-etch (SE), Xeno v, one component self-etching dental adhesive] and [Noetch (NE), Compobond1, prime& bond only]. Fifty human molars with occlusal caries were used to prepare dentin samples which were assigned to 5 groups: group I and III the prepared samples treated by CB and CS respectively then with TE, group II and IV the prepared samples treated by CB and CS respectively then with SE, while in group V the prepared samples treated by CS and then with NE. For each sample there was light cured composite core build up. After water storage, the samples were tested in a single-plane shear test assembly. The results demonstrated that there were statistical significant differences with in the mode of caries removal groups and also there were statistical significant differences between the bonding systems which affect SBS of carious dentin at p < 0.01, with in favor of the TE over SE. The present data demonstrate that with the use of CS on (carious dentin, there was either increase or decrease in bond strength in relation with different bonding systems.